2019
DOI: 10.1016/j.geomphys.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic T-duality

Abstract: We introduce the notion of crystallographic T-duality, inspired by the appearance of K-theory with graded equivariant twists in the study of topological crystalline materials. Besides giving a range of new topological T-dualities, it also unifies many previously known dualities, motivates generalisations of the Baum-Connes conjecture to graded groups, provides a powerful tool for computing topological phase classification groups, and facilitates the understanding of crystallographic bulk-boundary correspondenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
(140 reference statements)
1
9
0
Order By: Relevance
“…7.1) in the momentum space picture is T-dual to the geometrical restriction ι * in the position space picture, as is intuitively "obvious" and in the same vein as the results in [21]. In [18] we show further that "crystallographic T-dualities" exist for any crystallographic space group, and just as for pg, graded twists are essential in their formulation.…”
Section: A Crystallographic T-dualitysupporting
confidence: 70%
See 3 more Smart Citations
“…7.1) in the momentum space picture is T-dual to the geometrical restriction ι * in the position space picture, as is intuitively "obvious" and in the same vein as the results in [21]. In [18] we show further that "crystallographic T-dualities" exist for any crystallographic space group, and just as for pg, graded twists are essential in their formulation.…”
Section: A Crystallographic T-dualitysupporting
confidence: 70%
“…We have also given a glimpse of "crystallographic T-duality" in the case of G = pg, which was guided by the physical intuition of the bulk-boundary correspondence. In a subsequent work [18], we study such new dualities for general space groups, where further interesting phenomena arise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic T-duality isomorphisms K * (R/Z) ∼ = K * −1 ( Ẑ) can be formulated as a Fourier-Mukai transform, or as the Baum-Connes assembly map for Z composed with Poincaré duality. In [GT19], it was shown that every (ordinary) crystallographic space group G acting on d-dimensional Euclidean space V , induces crystallographic T-duality isomorphisms of twisted K-theories, (1.1) T G : K * +d,−v P (V /Π) → K * ,σ P ( Π).…”
Section: Introductionmentioning
confidence: 99%